(untitled) (Revista de Ensino em Artes, Moda e Design, 2026)
This article will unfold the concepts of complexity and open reason defended by Morin (2015) in order to support his dialogues with the fantastic thought of Gianni Rodari (1982), aiming to promote the exercise of complex thinking in the analysis of the book *Grammar of Fantasy*. Situated within the movement of cognitive migrations between various fields of knowledge, the book presents the methodological procedures of the Italian writer in promoting a multidimensional education focused on the subject and characterized by thinking with and within complexity. This dynamic will be examined in relation to the theoretical intersections that preceded teaching and learning processes in Visual Arts that are intended to be open and processual, focusing on treating the learner as the one who gives meaning to their own learning.